Extended phenotyping does not preclude the occurrence of delayed haemolytic transfusion reactions in sickle cell disease. (10th October 2021) - Gerritsma, Jorn; Bongaerts, Vera; Eckhardt, Corien; Heijboer, Harriet; Nur, Erfan; Biemond, Bart; van der Schoot, Ellen; Fijnvandraat, Karin; ,
Summary: Delayed haemolytic transfusion reaction (DHTR) is a potentially life‐threatening complication of red blood cell (RBC) transfusions in sickle cell disease (SCD) and is classically induced by reactivation of previously formed antibodies. Improved antigenic matching has reduced alloimmunization and may reduce DHTR risk. We conducted a retrospective cohort study to investigate the incidence rate of DHTR in SCD patients receiving extended matched units (ABO/RhDCcEe/K/Fy a /Jk b /S). Occasional transfusion episodes (OTE) between 2011 and 2020 were reviewed for occurrence of DHTR symptoms using four screening criteria: decreased Hb, increased lactate dehydrogenase (LDH), pain, and dark urine. We included 205 patients who received a cumulative number of 580 transfusion episodes of 1866 RBC units. During follow‐up, 10 DHTR events were observed. The incidence rate of DHTR was 13·8/1000 OTEs [95% confidence interval (CI): 7·37–22·2], with a cumulative incidence of 15·2% (95% CI: 8·4–24·0%) after 25 patients having received RBC units. One DHTR event was fatal (10%). Symptoms were misdiagnosed in four DHTR events (40%) as other acute SCD complications. Despite a lower incidence rate compared to most other studies, the incidence rate of DHTR in SCD remains high, in spite of extended matching of donor RBCs. Increased awareness of DHTR is of utmost importance to facilitate early diagnosis and, consequently, improve outcome.